In vitro dynamic degradation behavior of new magnesium alloy for orthopedic applications - Yang, Gui-Fu; Kim, Yu-Chan; Han, Hyung-Seop; Lee, Gwang-Chul; Seok, Hyun-Kwang; Lee, Jae-Chul (WILEY, 2015)
We report on methodologies for use in the design of a biodegradable Mg alloy appropriate for load-bearing but temporary orthopedic implant applications. Comparative studies of Mg-5Ca and Mg-5Ca-1Zn were conducted to explore the effects of a combination of minor alloying and hot extrusion, on the alloy's mechanical properties and corrosion resistance. The extruded Mg-5Ca-1Zn exhibited high ultimate compressive strength of 385 MPa and suffered no significant structural degradation even after immersion in simulated body fluid for 30 days. Mg-5Ca-1Zn alloy showed the mechanical strength and controlled corrosion rate to be considered as an ideal candidate for biodegradable orthopedic implant material. (c) 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 807-815, 2015.
Keywords: MECHANICAL-PROPERTIES; CORROSION PROPERTIES; CA ALLOYS; MICROSTRUCTURE; BIODEGRADATION; BIOMATERIALS